PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK DENGAN MODEL PROBLEM BASED LEARNING YANG MENGAKOMODASI KEMAMPUAN KOMUNIKASI MATEMATIS - Wahab, Saskia Damayanti; Mardiana, Dinny (Uninus Journal of Mathematics Education and Science (UJMES), 2023)
The main objective of this research was develop student worksheets that accommodate mathematical communication ability. The development of student worksheet following the Plomp research methode, which consists of two phases : preliminary research phase, and developing or prototyping phase. The data collection instruments used in this study were: a validation sheet to measure the validity by expert, and a questionnaire to measure the level of practicality by students and teachers. The result showed that student worksheets with the model of problem-based learning had been the requirement and eligibility based on the material and media expert assessment. Based on the research, developing student worksheets with problem-based learning had been the criteria of being valid and practical.